Impact of COVID-19 on the Speech and Language Therapy Profession and Their Patients - Chadd, Katie; Moyse, Kathryn; Enderby, Pam (Frontiers in Neurology, 2021)
The impact of COVID-19 on neuro-rehabilitation professions has been substantial. This paper reviews the contribution and role of speech and language therapy (SLT) at a time of disruption. Objective: To review the impact of COVID-19 on SLT provision in the United Kingdom (UK), and to assess the outcomes of SLT patients with and without COVID-19. Method: 1.The Royal College of Speech and Language Therapists’ (RCSLT) database of data from SLT services across the UK was interrogated to elicit information on patients receiving services prior to and during the pandemic, and patients with COVID-19. Findings are provided descriptively. 2.RCSLT members were distributed a survey at 6 weeks and 12 weeks after the pandemic hit the UK. Quantitative data was analysed thematically and is presented descriptively. Results: 1.The profile of patients accessing SLT before and after the pandemic began differs. However, the impact of therapy has not changed. Reasons for referral of COVID-19 patients varied, but notably included dysphagia and cognitive-communication disorder. 2.There were 544 respondents to the initial survey, and 413 to the second. Respondents referred to a number of changes, including: adopting more flexible approaches to service provision; reduced service provision to usual caseload and a reduction in patients’ access to treatment. Discussion: The pandemic has affected processes of care of those working within neuro rehabilitation. For SLT, referral patterns are different, usual care has been disrupted and interventions have been modified. These are likely to have an impact on patient outcomes both positively and negatively.